Effect of classical music on growth performance, stress level, antioxidant index, immune function and meat quality in broilers at different stocking densities - Gao, Xinlei; Gong, Jiangang; Yang, Bowen; Liu, Yanci; Xu, Hongjian; Hao, Yanshuang; Jing, Jialin; Feng, Zhihua; Li, Lihua (Frontiers in Veterinary Science, 2023)
High-stocking density is one of the factors that can easily cause oxidative stress and inflammatory reaction of broilers. Currently, music therapy has been proposed to help animals relieve stress to some extent. However, it is still unclear whether classical music can alleviate stress in broilers at high stocking densities. Hence, this study aimed to investigate the effects of classical music on growth performance, stress level, antioxidant index, immune function and meat quality of broilers under different stocking densities. A total of 540 one-day-old broilers with similar body weight were randomly divided into 6 treatment groups, with 6 replicates per group, which included two feeding environments (with/without classical music) and three stocking densities (15.5, 17.9, and 20.3 birds/m 2 ), thereby making a 2×3 factorial arrangement. The results showed as follows: increasing stocking density decreased the average daily feed intake and average daily gain (ADG), increased feed-to-gain ratio (F/G) and mortality of broilers. Moreover, increased density resulted in an increase in serum corticosterone (CORT) and adrenocorticotropic hormone (ACTH) levels. Increasing stocking density decreased spleen and bursal indices, serum immunoglobulin A (IgA), immunoglobulin G (IgG), and immunoglobulin M (IgM) levels. Increasing stocking density elevated serum malondialdehyde (MDA) and decreased catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) activities.Increasing stocking density decreased serum total protein (TP) levels and increased total cholesterol (TC) and glucose (GLU) levels. Additionally, increasing stocking density decreased the cooking liss of pectoralis and increased the L*24h value of pectoralis. Meanwhile, playing classical music for broilers increased their ADG and decreased F/G, and decreased serum CORT, ACTH, GLU content. In addition, the bursa of Fabricius index, serum IgA and IgG contents as well as the a*24h value of pectoralis was increased under the music therapy. In conclusion, high-stocking density (20.3 birds/m 2 ) harmed the growth performance and health of broilers, and the classical music stimulus ameliorated the negative effects to some extent.